Pengaruh Teknik Relaksasi Nafas Dalam Untuk Menurunkan Tingkat Nyeri Pada Pasien Post Operasi Kolesektomi - Listiyani, Dwi; Maria Astrid (CV. ULIL ALBAB CORP, 2025)
Nurses have a major role in providing nursing care to patients, one of which is that nurses can provide nursing actions to reduce pain levels in patients while in the treatment room, one of which is by conducting deep breathing relaxation nursing interventions. The purpose of this study was to determine the effect of deep breathing relaxation nursing interventions on reducing the pain scale in post-cholecystectomy patients at Hospital X. This study was conducted in the inpatient room on December 9-13, 2024. The method used in providing nursing care to post-cholecystectomy patients was carried out for 5 minutes. Respondents in this report were 1 adult patient aged 45 years with female gender and an adult aged 39 years with female gender. The results of the report show that after the assessment was carried out, it was found that post-cholecystectomy patients who were given deep breathing relaxation techniques could reduce pain levels with an initial scale of 5/10 to 3/10, while patients who were not given deep breathing relaxation techniques still felt the same pain with an initial pain scale of 4/10 still on a scale of 4/10, therefore nurses play an important role in providing nursing care to reduce pain levels in post-cholecystectomy patients.